2009
DOI: 10.1111/j.1528-1167.2008.01795.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcome after hemispherectomy in hemiplegic adult patients with refractory epilepsy associated with early middle cerebral artery infarcts

Abstract: SUMMARYPurpose: To study the outcome after hemispherectomy (HP) in a homogeneous adult patient population with refractory hemispheric epilepsy. Methods: Fourteen adult patients submitted to HP were studied. Patients had to be at least 18 years old, and have refractory epilepsy, clearly focal lateralized seizures and unilateral porencephalus consistent with early middle cerebral artery infarct on magnetic resonance imaging (MRI). All patients were submitted to functional hemispherectomy. We analyzed age of seiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 17 publications
1
16
0
1
Order By: Relevance
“…Several authors have advocated early hemispheric surgery and short epilepsy duration and some evidence seems to suggest advantages with regard to postoperative development and adaptive functioning 7 10 14–15 20–24 33. We found a slightly better seizure outcome in ES patients but reported better intellectual, academic and psychosocial outcomes for LS patients.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Several authors have advocated early hemispheric surgery and short epilepsy duration and some evidence seems to suggest advantages with regard to postoperative development and adaptive functioning 7 10 14–15 20–24 33. We found a slightly better seizure outcome in ES patients but reported better intellectual, academic and psychosocial outcomes for LS patients.…”
Section: Discussionmentioning
confidence: 57%
“…Advantageous cognitive and psychosocial outcomes in hemispherectomy patients operated at a higher age have been previously reported 29 33–38. For example, Cuckiert et al 33 found no cognitive decline in any of the 14 adult hemispherectomy patients. Chiricozzi et al 36 described a case of remarkable cognitive improvement after hemispherectomy at age 14 years, and Telfeian et al 34 reported recovery of language in a patient with hemispherectomy at age 16 years.…”
Section: Discussionmentioning
confidence: 99%
“…Hydrocephalus is commonly seen, as are infections, fever, anemia and temporary worsening of previous deficits [1], [15]. In adults, hemianopia, loss of pincer grasp and worsening gait, all expected effects of hemispherectomy [16], [17], cause more impairment than in children. However, overall motor and intellectual function has been seen to improve after surgery [17].…”
Section: Discussionmentioning
confidence: 99%
“…In adults, hemianopia, loss of pincer grasp and worsening gait, all expected effects of hemispherectomy [16], [17], cause more impairment than in children. However, overall motor and intellectual function has been seen to improve after surgery [17].…”
Section: Discussionmentioning
confidence: 99%
“…22 Most studies relate to children, three published adult studies reporting respectively four of four, five of nine and five of 12 patients becoming seizure free. [23][24][25] Multiple subpial transection aims to limit the horizontal spread of epileptiform activity across functional columns of eloquent cortex. A meta-analysis of adults and children has shown >95% seizure frequency reduction in 87% of patients with generalised seizures and 68% with partial seizures, compared to cortical transections alone.…”
Section: Historymentioning
confidence: 99%